Cyclone in the “Malvinas Islands” and the Spiral Galaxies - Ricardo Gobato; Abhijit Mitra; Alireza Heidari; Marcia Regina Risso Gobato (Journal of Weather Changes, 2022)
A subtropical cyclone is a weather system that has some characteristics of a tropical cyclone and some characteristics of an extratropical cyclone. They can form between the equator and the 50th parallel. In mathematics, a spiral is a curve which emanates from a point, moving farther away as it revolves around the point. The characteristic shape of hurricanes, cyclones, typhoons is a spiral. There are several types of turns, and determining the characteristic equation of which spiral the Extratropical Cyclone (EC) fits into is the goal of the work. The study demonstrates a double spiral for the extratropical cyclone, similarly Lindblad (1964) demonstrates a double spiral, to demonstrate the structure of spiral galaxies. Despite the data obtained in the EC that passed through the southern tip of South America west and east of the Falklands Islands, everything indicates that the short occurrence ECs indicate the double spiral structure, but with the structure of a Cote’s double spiral.
Keywords: Extratropical Cyclone